Mitochondrial Genome and Phylogenetic Analysis of the Narrownose Smooth-Hound Shark Mustelus schmitti Springer, 1939 - Walter Nisa-Castro-Neto; Paulo Guilherme Carniel Wagner; Diéssy Kipper; Vinicius Proença da Silveira; André Salvador Kazantzi Fonseca; Nilo Ikuta; Vagner Ricardo Lunge (Animals)
Southern Brazil is home to a large biodiversity of elasmobranchs from the Brazilian coast. Several genera and species of small sharks of the Triakidae family live in this marine environment. Studies on these shark species are scarce, with few genetic data and little information on animal population structures. The present study aimed to sequence the complete mitochondrial genome (mtDNA) of the endangered species Mustelus schmitti (narrownose smooth-hound shark) and to perform a phylogenetic analysis of the Triakidae family. The mtDNA sequenced here was 16,764 bp long and possessed the usual 13 mitochondrial protein coding genes (PCGs), 22 tRNAs, two rRNAs (12S and 16S) and a large D-loop DNA sequence, presenting an overall organization similar to other species from the genus Mustelus. Phylogenetic analyses were performed using a dataset containing this new mtDNA and 59 other mitochondrial genomes of the Carcharhiniformes species (including 14 from the Triakidae family), using the Maximum Likelihood (ML) method. All the species of the Triakidae family were clustered into a monophyletic topology group. In addition, polyphyly was observed in Galeorhinus galeus, Hemiatrakis japanica, Triakis megalopterus and Triakis semifasciata. In conclusion, this study contributes to a deeper understanding of the genetic diversity of sharks and represents an important step towards the conservation of these endangered animals.